قرآن کریم میں انبیاء کرام علیہم السلام کے عربی اور غير عربی نام ( اسماء معربہ) کا لغوی و اشتقاقی مطالعہ: Arabic and Non Arabic names of the holy prophets mentioned in the Holy Quran(linguistic and deriving study) (Khairulummah, 2023)
There is no doubt that The holy Quran is an unchallengeable revealed book consisting of rhetoric. And  eloquent. All Arabs tried his best to bring up with selfsame book or one verse in terms of eloquence and rhetoric but they defeat to do so.So The holy Quran mentioned twenty SIX prophets names, most of whom are mentioned in the Bible as well, (non -Arabic) . but these prophets also ,mentioned  in the holy Quran also, but what are their names in the Quran and the Bible,? We will discuss and answer these simple questions. to investigate about this wonderful and valuable topic in the holy Quran and discus about the names of the prophets which are used in the holy Quran in the Arabic language and non-Arabic.Selection of the name of the holy prophets was chosen due to the large number of Quranic verses. The research included on the introduction and on two kinds of prophets name: 1-Arabic these are:Adam,shuaib,Salih, Muhammad2-Non-Arabic these are: Ibrahim, Isaac,Moses,Aaron, Elias, Aadam Nooh,Idrees,Ismail,Yaqob,Yousaf,Loot,Hood,Dawod,Sulaiman,AyoobYounas,Yasaie,Yahya,Zakaya,uzair Eisa.